Use of the von Willebrand factor concentrate with low factor VIII content to manage patients with inherited von Willebrand disease requiring surgical or secondary long‐term prophylaxis: An expert opinion paper from an Italian panel. (24th May 2022) - Castaman, Giancarlo; Borchiellini, Alessandra; Coppola, Antonio; Cultrera, Dorina; Marino, Renato; Federici, Augusto B.; Giuffrida, Anna Chiara; Marchesini, Emanuela; Molinari, Angelo Claudio; Maria, Siboni Simona; Zanon, Ezio
Abstract: Objectives: The present review aims to summarize the state‐of‐the‐art von Willebrand disease (VWD) treatment focusing on specific clinical settings (obstetrics, surgery, long‐term prophylaxis and comorbidities) as well as on the use of a Von Willebrand factor (VWF) concentrate with low FVIII content. Methods: Literature research and case reports. Results and Conclusions: Considering that patients affected by VWD have an intact ability to synthesize FVIII, in order to avoid excessive levels of FVIII, a highly purified plasma VWF concentrate with low FVIII content could be particularly useful in those patients and clinical circumstances at high thrombotic risk as well as for long‐term prophylaxis. When deciding the optimal therapeutic strategy, physicians should take into account both the patient's history and the differences among available concentrates according to the clinical situations requiring treatment.